2008
DOI: 10.1080/10412905.2008.9699998
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition of Two Species ofEremostachysfrom Iran (E. adenanthaJaub. et Spach andE. macrophyllaMontbr. et Auch.)

Abstract: The essential oils of Eremostachys adenantha and Eremostachys macrophylla have been investigated by GC and GC/MS. Seventy-six compounds of E. adenantha and thirty-five of E. macrophylla representing 91.2% and 92.9% of the oils were identified, respectively. The main constituents of the oil of E. adenantha were dodecanal (12.7%), hexadecanoic acid (9.9%) and 6,10,14-trimethyl-2-pentadecanone (9.0%); while for E. macrophylla, they were spathulenol (23.4%), hexadecanoic acid (13.5%) and caryophyllene oxide (9.3%). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
4
3
Order By: Relevance
“…These constituents were different from those seen in previous studies on the same species [32][33][34]. Based on various parameters like time of collection, climate and the ground composition of the sampling area, in addition to the growth stages of the plant, chemical composition of the essential oil of the same species can change [35].…”
Section: Sn Plant Speciescontrasting
confidence: 45%
“…These constituents were different from those seen in previous studies on the same species [32][33][34]. Based on various parameters like time of collection, climate and the ground composition of the sampling area, in addition to the growth stages of the plant, chemical composition of the essential oil of the same species can change [35].…”
Section: Sn Plant Speciescontrasting
confidence: 45%
“…This study showed considerable amounts of hexadecanoic acid (27.5%), ethyl linoleate (8.5%), 6-methyl-α-ionone (8.0%). These major constituents were different from those seen in previous studies on the same species [5][6][7]. These results demonstrated that the chemical composition of the essential oil of the same species can change depending on a variety of conditions, including climate, time of collection, and the ground composition of the sampling area, in addition to the growth stages of the plant.…”
Section: Resultscontrasting
confidence: 94%
“…It is evident from the above data, that there are significant differences in the results of the current study with previous ones [5][6][7] for the aerial parts of E. macrophylla. There may be differences related to environmental conditions such as climate, altitude, collection time, ground composition of the sampling area and different growth stages such as pre-flowering, fresh flowering and air-dried-flowering stages.…”
Section: Introductioncontrasting
confidence: 93%
See 2 more Smart Citations